2000
DOI: 10.1155/2000/467567
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Biliary Strictures to Determine the Predictors of Malignancy

Abstract: A serum bilirubin level of 75 micromol/L or higher, or a stricture length of greater than 14 mm was highly predictive of malignancy in patients with a biliary stricture. Ultrasound was useful in predicting malignant strictures by detecting either intrahepatic duct dilation or by visualizing the tumour (primary or metastases). Strictures with a 'benign' cholangiographic appearance are frequently malignant. Disida scan did not add additional information. ERCP is necessary to diagnose benign strictures, which ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
2
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 13 publications
5
23
2
1
Order By: Relevance
“…Previous studies have also found bilirubin to predict malignancy with AUC values of 0.8 5 and quoted bilirubin levels of 84 mmol/l (sensitivity and specificity of 98.6% and 59.3%, respectively) and 75 mmol/l. 6,7 These values are commensurate with the results from the current data. A previous study has reported that patients presenting with malignant obstructive jaundice have a median bilirubin level of 160 mmol/l and that only 23% of patients have a bilirubin level <100 mmol/l and a rate of rise of bilirubin of 100 mmol/l per week.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have also found bilirubin to predict malignancy with AUC values of 0.8 5 and quoted bilirubin levels of 84 mmol/l (sensitivity and specificity of 98.6% and 59.3%, respectively) and 75 mmol/l. 6,7 These values are commensurate with the results from the current data. A previous study has reported that patients presenting with malignant obstructive jaundice have a median bilirubin level of 160 mmol/l and that only 23% of patients have a bilirubin level <100 mmol/l and a rate of rise of bilirubin of 100 mmol/l per week.…”
Section: Discussionsupporting
confidence: 89%
“…[5] In the present study, serum bilirubin levels were significantly elevated in malignant group; however, elevation in liver enzymes was statistically not significant. Mansfield et al .…”
Section: Discussioncontrasting
confidence: 63%
“…The threshold values of liver function tests used for comparison between positive and negative for malignancy were as follows-serum bilirubin (75μmol/L = 4.5 mg/dL); alanine transaminase (ALT) (100 U/L); aspartate transaminase (AST) (150U/L) and alkaline phosphatase (ALP) (400 U/L). [5] Statistical analysis was carried out using the SPSS17.0 version and results were compared between groups using χ 2 test wherever required.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, we found no earlier studies on the role of intrahepatic bile ducts in this differential diagnosis, but we did found two studies which had been designed to compare the occurrence of intrahepatic bile duct dilatation between patients with malignant and benign bile duct strictures 3,4 . In these studies, intrahepatic bile duct dilatation was more frequently ( P = 0.002, P < 0.0001; subsequently) encountered in malignant biliary strictures (93%, 74%; subsequently) compared with benign biliary strictures (36%, 40%; subsequently).…”
Section: The Number (Percentage) Of Patients With Non‐dilated and Witmentioning
confidence: 95%